Deconfinement of Quarks and Gluons in Nucleus-nucleus Collisions - Gorenstein, M.I. (Ukrainian Journal of Physics, 2022)
The energy dependence of hadron production in relativistic nucleus-nucleus collisions reveals the anomalies. They were predicted as the signals of the deconfinement phase transition and observed by NA49 collaboration in Pb + Pb collisions at the CERN SPS. This indicates the onset of the deconfinement in central nucleus-nucleus collisions at about 30 AGeV.